(untitled) (Costos y Gestión, 2020)
The main objective of this paper is the assessment of COVID-19 economic impact and its hit on companies’ management and performance, through literature analysis, cases review and a field research in order to suggest concrete actions for its implementation in firms. Pandemic is a «transforming catastrophic event» with a huge impact on mankind. Plunging demand, raising unemployment and loss of income affect millions; uncertainty on potential recovery and on future itself, dominate current environment. But tragedy must not prevent deciding and executing. Business management in crisis mode forces to develop concrete actions to primarily survive, while being highly focused on cash flow, cost management and reduction, usage of specific techniques and tools, and monitoring performance thorough dashboards and key indicators. New consumer behaviors, widely adopted technology and automation, different ways of promoting, marketing and sales channels, innovative working models for employees such as «distributed work» and «remote work», and economic sectors that will be seriously affected and will be reconverted, do represent trends already in place which could happen to stay in the near future. Key conclusion for all firms, managers and employees is the importance of adapting to the «new reality», assuming flexible and resilient positions, making wise decisions and implementing appropriate actions today, as these two factors will significantly influence both immediate future and medium-term results.